(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2025)
Gastrointestinal parasites (GIPs) are the major impediment to livestock production in Nigeria. The damage caused by these parasites often results in huge economic loss and some of the GIPs of cattle are great concern to public health. Hence, this study inves- tigated the prevalence and polyparasitism of GIP among cattle in Gombe metropolis. Between May and November 2021, 350 fecal samples were collected randomly from herder’s cattle (202) and trader’s cattle (148), and examined for GIP ova and oocysts using direct wet mount and concentration technique. Factors such as breed, sex, and age were obtained. The overall prevalence of GIPs was 74.3% while there was higher prevalence (79.2%) among herder’s cattle than trader’s cattle (67.6%), and more female (75.2%) were infected than male (73.8%). There were no significant differences (p ≥ 0.05) between the prevalence obtained in the location, sex, and age of the cattle. However, GIPs prevalence among the Red Bororo (84.4%) was significantly higher (p < 0.05) than that of White Fulani (73.0%) and Sokoto Gudali (69.6%) cattle. A variety of GIPs ova and cysts were detected which includes trematodes: Fasciola spp. (4.9%), Schistosoma bovis (3.8%), and Paramphistomum spp. (2.2%); cestodes: Taenia saginata (6.3%), Hymenolopsis spp. (3.7%), and Monezia spp. (2.9%); nematodes: Ascaris spp. (4.9%), Gongylonema spp. (4.9%), Strongyloides spp. (4.9%), Trichuris spp. (4.5%), Nematodirus spp. (2.2%), Trichostrongylus spp. (1.1%), Ostertagia spp. (1.1%), and Toxocara spp. (0.6%); and coccidians: Eimeria spp. (2.2%) and Sarcosystis spp. (1.1%). Moreover, the prevalence of mono infection (52.0%) was significantly higher (p < 0.05) than polyparasitism (22.3%). This study revealed a high prevalence of GIPs among cattle in Gombe metropolis. Therefore, prevention and control of parasitic infestations, regular deworming, good husbandry management, and practices are advocated and should be encouraged through extension services.